Gaya Komunikasi Suster Yunior SCMM - Soares, Fatima Asni; Salman, Doddy (Kiwari, 2025)
A nun has her own charm, besides having a communication style that is identical to gentleness and friendliness. Good communication can not only build positive communication and relationships but can also facilitate the process of nun service in her mission. In community life, differences in age, culture can trigger conflicts in living together, so communication is practiced at the beginning of formation. This study aims to identify the communication styles of SCMM Junior Sisters in everyday life. This study uses a qualitative approach, data processing, observation, documentation, and interviews from original sources. The main informants were two junior sisters from the SCMM congregation who work in North Jakarta. From the results of this study, six communication styles were found that were often used by SCMM Junior Sisters, namely: Dramatic, Animated, Open, Relaxed, Attentive, Impression Leaving and Friendly communication styles. Communication style is very effective for the lives of junior sisters in the SCMM congregation. Dramatic and Animated communication styles are used by sisters in delivering teachings, while Open and Relaxed communication styles are used to build relaxed and open relationships. Meanwhile, the Attentive communication style shows concern and support for sisters who are grieving or in despair, and the Impression Leaving and Friendly communication styles leave a positive impression. Seorang biarawati memiliki daya tarik tersendiri, selain itu memiliki gaya komunikasi yang identik dengan kelembutan dan keramahan. Komunikasi yang baik tidak hanya dapat membangun relasi yang positif tetapi dapat mempermudah proses pelayanan biarawati dalam perutusannya. Dalam kehidupan berkomunitas perbedaan usia, budaya dapat memicu konflik dalam hidup bersama, maka komunikasi dipraktekan di awal pembinaan. Penelitian ini bertujuan untuk mengidentifikasi gaya komunikasi para Suster junior SCMM dalam kehidupan sehari-hari. Penelitian ini menggunakan pendekatan kualitatif, pengolahan data, observasi, dokumentasi, dan wawancara dari sumber asli. Informan utama adalah dua suster yunior dari kongregasi SCMM yang berkarya di Jakarta Utara. Dari hasil penelitian ini ditemukan enam gaya komunikasi yang sering digunakan oleh para suster junior SCMM yakni: Gaya komunikasi Dramatic, Animated, Open, Relaxed, Attentive, Impression Leaving dan Friendly. Gaya komunikasi sangat efektif bagi kehidupan suster yunior di dalam kongregasi SCMM. Gaya komunikasi Dramatic dan Animated digunakan para suster dalam menyampaikan ajaran, sedangkan gaya komunikasi Open dan Relaxed digunakan untuk membangun hubungan yang santai dan terbuka. Sedangkan gaya komunikasi Attentive menunjukkan perhatian dan dukungan bagi suster yang sedang berduka atau sedang putus asa, dan gaya komunikasi Impression Leaving dan Friendly meninggalkan kesan positif.